2014
DOI: 10.1162/asep_a_00279
|View full text |Cite
|
Sign up to set email alerts
|

Adoption, Adaptive Innovation, and Creative Innovation Among SMEs in Malaysian Manufacturing

Abstract: We categorized innovating firms in an ascending order as adopters, adapters, and creators to examine factors motivating these activities. For small firms, creation and adaption were significantly correlated with export orientation, engaging in collaborative research and development (R&D), receiving technical support from outside agencies, gaining technology from parent establishments, and supplying parts to multinationals. For medium-sized firms, R&D incentives, collaborative research, and accessing technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Bessonova and Gonchar ( 2017 ) 49. Hosseini and Narayanan ( 2014 ) 50. Antikainen and Vaataja ( 2010 ) 51.…”
Section: Demographics Of the Literature Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bessonova and Gonchar ( 2017 ) 49. Hosseini and Narayanan ( 2014 ) 50. Antikainen and Vaataja ( 2010 ) 51.…”
Section: Demographics Of the Literature Resultsmentioning
confidence: 99%
“…Importance, relevance, and clear need The dominant attainment task value as gleaned from the literature is the importance, relevance, and clear need for innovative behavior and goals (Aarikka-Stenroos et al, 2017;Hosseini & Narayanan, 2014). To this end, studies suggested that clear links to desired goals like careers or mastery (Aarikka-Stenroos et al, 2017;Edwards et al, 2014;Sorice & Donlan, 2015;Xie & Reider, 2014) and easy to see logic to how the innovation would be important to society, with a particular emergent theme of social justice and conservation causes (Antikainen & Vaataja, 2010;Reznickova & Zepeda, 2016;Sorice & Donlan, 2015).…”
Section: Strategies For Building Attainment Valuementioning
confidence: 99%
“…It is important to study OI within SMEs operating in various sectoral settings as research shows that differences in generated insights are often due to the unique characteristics of specific types of industries, for example, high-tech (Colombo et al, 2014;Rolandsson et al, 2011) versus low-tech and medium-tech sectors (Dodourova and Bevis, 2014), service-dominated industries versus manufacturing-based sectors (Hosseini and Narayanan, 2014), R&D-intensive in life sciences sector (Marangos and Warren, 2017), etc.…”
Section: Sectoral Patternsmentioning
confidence: 99%
“…Cheung and Lin 2004;Chen and Fang 2016) and the potential effects can be both positive and negative. There is a high degree of persistence in the innovative behavior of MNEs (Hosseini and Narayanan 2014). MNEs, through FDI, transfer knowledge, the results of innovation, to host countries and contribute to the technological upgrading of host countries (Findlay 1978;Wang et al 2014;Chen and Fang 2016).…”
Section: Fdi and Innovationmentioning
confidence: 99%